2015
DOI: 10.1039/c5cc01364j
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective fluorescence imaging of zinc distribution in HeLa cells and Arabidopsis using a naphthalene-based fluorescent probe

Abstract: 2-(N,N-Dimethylamino)naphthalene-based probe 1 was found to exhibit a dramatic enhancement in fluorescence upon addition of Zn(2+), but not with any other metal ions. Probe 1 as a chemoprobe enabled high-resolution fluorescence imaging of zinc ions in HeLa cells and Arabidopsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Fluorescent probe has been evaluated as the most powerful tool to monitor biologically relevant species for their high sensitivity and spatial resolution (Egawa et al, 2013; Chen et al, 2013; Radford et al, 2013; Huang et al, 2013; Bae et al, 2013; Jung et al, 2014; Zhang et al, 2014; Hettiarachchi et al, 2014; Zhou et al, 2014). During last years, lots of fluorescent probes for Zn 2+ have been developed to detect the cytosolic Zn 2+ to understand its role in living system (Zhang et al, 2014; Hettiarachchi et al, 2014; Zhou et al, 2014; Qian et al, 2009; Du et al, 2010; Meng et al, 2012; Guo et al, 2012; Lin et al, 2013; Divya et al, 2014; Hagimori et al, 2015; Lee et al, 2015). Unfortunately, most of the reported Zn 2+ fluorescent probes failed to target the mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent probe has been evaluated as the most powerful tool to monitor biologically relevant species for their high sensitivity and spatial resolution (Egawa et al, 2013; Chen et al, 2013; Radford et al, 2013; Huang et al, 2013; Bae et al, 2013; Jung et al, 2014; Zhang et al, 2014; Hettiarachchi et al, 2014; Zhou et al, 2014). During last years, lots of fluorescent probes for Zn 2+ have been developed to detect the cytosolic Zn 2+ to understand its role in living system (Zhang et al, 2014; Hettiarachchi et al, 2014; Zhou et al, 2014; Qian et al, 2009; Du et al, 2010; Meng et al, 2012; Guo et al, 2012; Lin et al, 2013; Divya et al, 2014; Hagimori et al, 2015; Lee et al, 2015). Unfortunately, most of the reported Zn 2+ fluorescent probes failed to target the mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is not clear how the trace elements are fixed to melanosomes, a metal binding property of melanin in the eye has been well established at least for the following 23 elements: Ag 25 , Al 25 , Ca 25 26 27 , Cr 25 , Cs 25 , Cu 25 28 29 , Fe 25 26 30 , Ga 25 , Hg 25 , K 25 27 , Mg 27 , Mn 25 30 31 , Rb 25 , S 26 , Sr 25 , Ni 25 , Pb 25 , Pd 25 , Pt 25 , Ti 25 , Tl 25 , V 25 , Zn 25 27 28 29 . Previously, zinc ion distribution has been studied using different fluorescent indicators, revealing a punctate cytoplasmic distribution in mouse fibroblasts 11 as well as its localization to the endoplasmic reticulum and mitochondria in HeLa cells 32 . Although no nuclear signal has been detected in this previous study, our μ-XRF images showed zinc signals in the nuclei of retinal cells, in addition to a punctate cytoplasmic signal ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of UO 2 2+ in the presence of Ca 2+ and Rb + resulted in a slight fluorescence quenching of 1 at 510 nm; however, other metal ions did not induce such fluorescence quenching effect at 510 nm. In general, UO 2 2+ is known as a hard Lewis acid, such that the nitrogen and oxygen atoms of the N , N ‐bis(acetic acid)aniline moiety of 1 can be effective for selective binding of UO 2 2+ according to the hard soft acid base theory, which were confirmed in the previous studies . These results demonstrated that the fluorescence intensity of probe 1 was effectively enhanced by UO 2 2+ with such a metal ion as the background.…”
Section: Methodsmentioning
confidence: 99%